The reality game : how the next wave of technology will break the truth - Woolley, Samuel (PublicAffairs, 2020)
"Despite all the attention paid to it, the problem of online disinformation is only getting worse. Social media may well play a role in the 2020 presidential election and other major political events. But that doesn't begin to describe what future propaganda will look like. As Samuel Woolley shows, we will soon be navigating new technologies such as human-like automated voice systems, machine learning, "deepfake" AI-edited videos and images, interactive memes, virtual reality and augmented reality. In stories both deeply researched and compellingly written, Woolley describes this future, and parses how the technology can be manipulated, who might control it, and its impact on political strategy. Finally, Woolley proposes strategic responses to this threat with the ultimate goal of empowering activists and pushing technology builders to design for democracy. We may not be able to alter how the internet was used to challenge democracy during elections or crises in years past, but we can follow signals to prevent manipulation in the future--and to use these powerful new tools not to control people but to empower them"--